Development and application of an enzyme immunoassay for the detection of the mycotoxin Fumigaclavine A - Latif, Hadri; Justus Liebig University Giessen (My University, 2010)
The present study describes the development of specific polyclonal antibodiesagainst fumigaclavine A (FuA) in rabbits, and the development of a highly sensitiveenzyme immunoassay (EIA) for this mycotoxin. The Mannich condensationreaction with formaldehyde was used to conjugate FuA to keyhole limpethemocyanin (KLH) as the immunogen, and to bovine serum albumine (BSA) for asthe coating antigen. Conjugation of FuA to KLH with formaldehyde proved to be aneffective approach for the preparation of immunogen for anti-FuA antibodyproduction.A competitive indirect EIA was optimized using antiserum obtained from onerabbit. The EIA was very sensitive for FuA, with a 50% inhibition concentration(IC50) value of 3.3 ng/ml and a detection limit of the standard curve in buffersolutions of 0.5 ng/ml. The EIA was very specific for FuA with 1.3%, 12.6%, and0.2% cross-reactivity with FuB, FuC, and FuD, respectively. IsoFuA and severalother lysergic acid derivatives (ergonovine, ergotamine, and alpha-ergocryptine)were tested but did not cross-react in this assay.The EIA was applied to the analysis of FuA in silage and in tissue from therespiratory system of birds with aspergillosis. The detection limit for FuA in silagewas at 10 ng/g, average recoveries from artificially contaminated control sampleswere 77.8%. None of 24 analyzed silage samples contained detectable amounts ofFuA. Although the number of samples was limited, the results indicate that there isnot a widespread problem of FuA in silage.The detection limit of the assay for FuA in tissue from the respiratory system ofbirds was at 1.5 ng/g, with average recoveries from artificially contaminated of92.7%. FuA was found in 66% tissue samples of aspergillosis cases. Cultivation offungal growth on respiratory tissue samples of aspergillosis cases on malt extractagar (MEA) yielded fungal material which was typical for A. fumigatus. When themycelium was extracted and assayed by FuA EIA, high amounts of FuA was found(up to 8 mg/g mycelium). Further analysis of the mycelium extract by HPLC foundFuA, FuC, and other unidentified compounds. Hydrolysis of FuC which have beenisolated from mycelium extract of A. fumigatus gave a new fumigaclavinederivative. FuD is proposed as the name of this compound.Different specificity pattern of the FuA EIA and that of a previously developedergonovine EIA were studied. In competitive indirect EIA, the anti-FuA antibody diddetect neither ergonovine nor IsoFuA. Conversely, by competitive direct EIAformat, the anti-ergonovine antibody was able to detect both FuA and IsoFuA.Using these assays in combination with HPLC separation of cheese extracts, aseries of blue-veined cheeses from the German market were analyzed. None of 16blue-veined cheese samples contained FuA. However, the presence of IsoFuA inblue-veined cheese samples was detected using the ergonovine EIA.This is the first description of antibodies against FuA and the first development ofan EIA for FuA. This is also the first report demonstrating that FuA is correlatedwith aspergillosis in birds. However, the role of this mycotoxin in this diseaseremains to be clarified.

Die vorliegende Arbeit beschreibt die Herstellung spezifischer Antikörper gegenFumigaclavin A (FuA) und die Entwicklung eines hochempfindlichen Enzymimmuntests(EIA) für dieses Mykotoxin. Die Mannich-Kondensation mitFormaldehyd wurde verwendet, um Fumigaclavin A an keyhole limpet hemocaynin(KLH) als Immunogen und an bovines Serumalbumin (BSA) alsBeschichtungsantigen zukoppeln. Die Kopplung von FuA an KLH mittelsFormaldehyd erwies sich als effektiver Ansatz zur Herstellung eines Immunogenszur Gewinnung von Anti-FuA Antikörpern in Kaninchen.Ein kompetitiver indirekter EIA wurde erstellt und optimiert, unter Verwendungpolykloner Antikörper eines Kaninchens. Der EIA war sehr empfindlich für FuA, miteiner 50%-Dosis von 3,3 ng/ml und einer Nachweisgrenze von 0,5 ng/ml (inPufferlösung). Der EIA war relativ spezifisch für FuA, mit Kreuzreaktionen von1,3%, 12,6% bzw. 0,2% Kreuzreaktion für FuB, FuC bzw. FuD. IsoFuA und einigeandere getestete Lysergsäurederivate (Ergonovin, Ergotamin, und alpha-Ergokryptin) wurden ebefalls untersucht, zeigten aber keine Kreuzreaktion indiesem Testsystem.Der EIA wurde zur Untersuchung von FuA in Silage und in Gewebsproben(Repirationstrakt) von Vögeln mit Aspergillose eingesetzt. Die Nachweisgrenze fürFuA in Silage betrug 10 ng/g, die durchschnittlichen Wiederfindungsraten für FuAin künstlich kontaminierten Kontrollproben lagen bei 77,8%. Keine der 24untersuchten Proben enthielt nachweisbare Gehalte an FuA. Obwohl nur einebegrenzte Probenanzahl untersucht wurde, zeigen die Ergebnisse, dass FuA keinweit verbreitetes Problem in Silage darstellt.Die Nachweisgrenze für FuA in Gewebsproben des Repirationstrakts von Vögelnlag bei 1,5 ng/g, mit durchschnittlichen Wiederfindungsraten für FuA in künstlichkontaminierten Proben von 92,7%. FuA wurde in 66% der Proben von Vögeln mitAspergillose nachgewiesen. Bei einer Kultivierung von Pilzisolaten desAtmungstraktes auf Malzextraktagar (MEA) entwickelte sich ein Mycel, das typischfür A. fumigatus war. Bei Extraktion des Mycels und Untersuchung im FuA-EIAwurden große Mengen an FuA (bis zu 8 mg/g Mycel) nachgewiesen. Bei einerweiteren Untersuchung des Mycelextrakts mittels HPLC wurden FuA, FuC undandere, nicht identifizierte Komponenten gefunden. Eine Hydrolyse von FuC, dasaus dem Mycelextrakt von A. fumigatus gewonnen wurde, ergab ein neuesFumigaclavin-Derivat. FuD wird als Name für diese Verbindung vorgeschlagen.Zur Untersuchung von Blauschimmelkäse auf Clavin-Alkaloide wurden dieunterschiedliche Spezifitäten des FuA-EIA und eines zuvor entwickeltenErgonovin-EIA ausgenutzt. Im kompetitiven indirekten EIA für FuA waren alleProben negativ. Dagegen wurde bei Verwendung eines kompetitiven direkten EIAunter Verwendung von Anti-Ergonovin-Antikörpern hohe Meßwerte erzielt. Beieiner Untersuchung mit Hilfe dieser beiden Testsysteme und einer HPLCTrennungvon Käse-Extrakten wurden Blauschimmelkäse des deutschen Marktesuntersucht. Keine der 16 untersuchten Proben enthielt FuA, jedoch wurde dieAnwesenheit von IsoFuA in Blauschimmelkäse nachgewiesen.Die vorliegende Arbeit beschreibt erstmals die die Entwicklung von Antikörperngegen FuA und eines Enzymimmuntests für dieses Mykotoxin. Auch wirderstmalig eine Korrelation zwischen FuA-Gehalten in Gewebe desRepirationstrakts und der Aspergillose von Vögeln beschrieben. Die Rolle diesesMykotoxins bei diesem Krankheitsbild bleibt allerdings noch zu klären.
Keywords: ddc:630